Diffuse Leptomeningeal Glioneuronal Tumor: A Rare Case Report with Review of Literature - Patankar, Amey P.; Vaghela, Palak; Nasit, Jitendra; Gohil, Rajvee (Asian Journal of Neurosurgery, 2022)
Diffuse leptomeningeal glioneuronal tumor (DLGNT) is a rare tumor that was defined as a separate entity in the 2016 World Health Organization classification of brain tumors. It is most common in the pediatric age group. The diagnosis of this tumor can be made preoperatively by its characteristic imaging findings of diffuse intracranial and intraspinal nodular leptomeningeal thickening and enhancement associated with small cyst-like nonenhancing lesions in the brain and spinal cord. We report a case of DLGNT in a 7-year-old male presenting with hydrocephalus. The patient was treated successfully by cerebrospinal fluid (CSF) diversion followed by biopsy of the lesion from the cerebellum. Histopathology and immunohistochemistry confirmed the diagnosis of DLGNT. Our case would hopefully increase the awareness regarding this rare tumor and facilitate an early diagnosis and management of the affected patients with atypical radiological features.
Keywords: glioneuronal tumor; diffuse glioneuronal leptomeningeal tumor; pediatric brain tumor; WHO classification of brain tumor; glial tumor